2013
DOI: 10.1128/aac.00594-13
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactam Antibiotics Targeting PBP1 Selectively Enhance Daptomycin Activity against Methicillin-Resistant Staphylococcus aureus

Abstract: The activity of daptomycin (DAP) against methicillin-resistant Staphylococcus aureus (MRSA) is enhanced in the presence of subinhibitory concentrations of antistaphylococcal ␤-lactam antibiotics by an undefined mechanism. Given the variability in the penicillin-binding protein (PBP)-binding profiles of different ␤-lactam antibiotics, the purpose of this study was to examine the relative enhancement of DAP activity against MRSA by different ␤-lactam antibiotics to determine if a specific PBP-binding profile is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 40 publications
(53 reference statements)
4
54
2
Order By: Relevance
“…S. aureus strains D592 and D712 are paired isogenic MRSA isolates from a clinical series using DAP plus antistaphylococcal ␤-lactam in refractory bacteremia (3). Strain D592 is the DAP-susceptible index isolate, whereas D712 is a subsequent isolate that had become DNS as well as vancomycin intermediate following multiple unsuccessful antimicrobial regimens, as previously characterized (13). The genetic relatedness of the two patient isolates was confirmed by whole-genome sequencing (21).…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…S. aureus strains D592 and D712 are paired isogenic MRSA isolates from a clinical series using DAP plus antistaphylococcal ␤-lactam in refractory bacteremia (3). Strain D592 is the DAP-susceptible index isolate, whereas D712 is a subsequent isolate that had become DNS as well as vancomycin intermediate following multiple unsuccessful antimicrobial regimens, as previously characterized (13). The genetic relatedness of the two patient isolates was confirmed by whole-genome sequencing (21).…”
Section: Methodsmentioning
confidence: 79%
“…The demonstrated effectiveness of this combination therapy despite heterogeneity in the specific ␤-lactam employed reflects the possibility that DAP-␤-lactam synergy may be a ␤-lactam class effect. However, a recent study observed significant diversity among different ␤-lactams in their relative efficacies in combination with DAP and reported that synergy is dependent on the relative affinity of a ␤-lactam for PBP1 (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may prevent the development of daptomycin resistance [96]. A recent article suggests that this benefit is particular for those b-lactams that bind to penicillin binding protein-1 (PBP1) [99].…”
Section: Combination Therapy With Daptomycinmentioning
confidence: 99%
“…We previously observed that DAP-mediated sensitization to ␤-lactams occurred with those ␤-lactams that preferentially target PBP 1 or PBP 2, including NAF (PBP 1, PBP 2), IPM (PBP 1), and CTX (PBP 2), whereas no changes were observed with ␤-lactams targeting PBP 4, such as cefoxitin (FOX), or PBP 3, such as cefaclor (CEC) (8,21,22). Similar effects were observed in other in vitro-selected DAP r mutants obtained from DAP s CB1631 (DAP r CB1631 mutants) and CB5011 (DAP r CB5011 mutants) (8).…”
mentioning
confidence: 99%